2019
DOI: 10.3389/fphar.2019.00640
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Proteomics Approach Characterizes the Dual Functionality of miR-328 in Monocytes

Abstract: MicroRNAs (miRs) are small noncoding RNAs which control the expression of target genes by either translational repression or RNA degradation, known as canonical miR functions. The recent discovery that miR-328 has a noncanonical function and can activate gene expression by antagonizing the activity of heterogeneous ribonuclear protein E2 (hnRNP E2) opens an unexplored and exciting field of gene expression regulation. The global importance of such noncanonical miR function is not yet known. In order to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…A FC cutoff of ≥1.25 for overexpression and ≤0.8 for the downregulation of proteins was selected to be biologically significant, and an adjusted p -value, that is, q ≤ 0.05, was selected for statistical significance. A similar range of FCs has been previously reported by studies using isobaric labeling. Rotenone treatment highlighted 421 differentially regulated proteins (FC ≥1.25 or ≤0.8), of which 144 were significantly altered ( q ≤ 0.05, with respect to untreated cell control, Figure B). Yashtimadhu choorna extract cotreatment was found to significantly regulate 88 proteins ( q ≤ 0.05, with respect to rotenone), which included restoration of 84 proteins that were dysregulated by rotenone and an additional regulation of 4 proteins (Figure C).…”
Section: Results and Discussionsupporting
confidence: 82%
“…A FC cutoff of ≥1.25 for overexpression and ≤0.8 for the downregulation of proteins was selected to be biologically significant, and an adjusted p -value, that is, q ≤ 0.05, was selected for statistical significance. A similar range of FCs has been previously reported by studies using isobaric labeling. Rotenone treatment highlighted 421 differentially regulated proteins (FC ≥1.25 or ≤0.8), of which 144 were significantly altered ( q ≤ 0.05, with respect to untreated cell control, Figure B). Yashtimadhu choorna extract cotreatment was found to significantly regulate 88 proteins ( q ≤ 0.05, with respect to rotenone), which included restoration of 84 proteins that were dysregulated by rotenone and an additional regulation of 4 proteins (Figure C).…”
Section: Results and Discussionsupporting
confidence: 82%
“…Interestingly, the decoy mechanism of miR-328 and hnRNP E2 affects a variety of targets and cellular processes (Saul et al, 2016(Saul et al, , 2019b while in this case the decoy of miR-574-5p and CUGBP1 seems to be quite specific for mPGES-1. Retrospectively, this is consistent with one of our previous studies in which we firstly demonstrated that miR-574-5p prevents CUGBP1 from binding to mPGES-1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be mentioned that mPGES-1 did not reveal this pattern in the proteomics data. We would like to point out that a proteomics study, even if we have used an established method (Eriksson et al, 2008;Ochs et al, 2013;Bergqvist et al, 2019;Saul et al, 2019b), only provides initial indications of which proteins could be regulated. It does not map the exact expression changes, which is a common limitation of this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-328 has been reported to function as a cancer-related miRNA. MiR-328 could increase reactive oxygen species (ROS) production and promote the adhesion and migration ability of monocytes during monocyte maturation (13). In lung cancer, miR-328 expression was significantly elevated and could promote cell migration (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%